Understanding the impact of fire on termites in degraded tropical peatlands and the mechanisms for their ecological success: current knowledge and research needs. Issue 5 (14th July 2015) - Neoh, Kok‐Boon; Bong, Lee‐Jin; Muhammad, Ahmad; Itoh, Masayuki; Kozan, Osamu; Takematsu, Yoko; Yoshimura, Tsuyoshi
Abstract: Peatlands have experienced large scale changes due to extensive deforestation for logging, conversion to agro‐industrial plantations, and frequent peat fires. The adverse effects of peat fires can lead to long‐term impacts on invertebrate biodiversity in the peatland ecosystem. Although the impact of fire on termite diversity in tropical grasslands and savannas has been the focus of increased attention in recent years, little is known about the effects of peat fires on termite assemblages. In this review, we present available information about the impact of human use of peatlands on termite assemblages in the Indo‐Malayan region. By synthesizing the currently available studies conducted in temperate and tropical savanna systems, we highlight the need for studies of the relationship between termites and fire‐impacted tropical peatlands. We consider the ecological and biological scenarios in fire‐impacted peatland that are likely to shape termite assemblages, and we discuss traits of the surviving genera (i.e., Coptotermes, Schedorhinotermes, and Parrhinotermes ) that may contribute to their success in the harsh post‐fire peatland environment (e.g., colony fusion, colony breeding structure, subsidiary nests, and colony migration). Knowledge of these strategies is crucial for understanding the evolutionary adaptation process of termites. This review also aims to stimulate further research in using termite ecosystem services to restore the fertility of degraded fire‐impacted peatlands.